(untitled) (Research, Society and Development, 2022)
This study starts from the intention of investigating and discussing inclusive education and the participation of students with Autism Spectrum Disorder (ASD) in two schools in the city of Belém-PA under the eyes of teachers. The research is of a qualitative nature, based on a semi-structured interview with teachers who work in regular education (elementary 2) in two schools in Belém. The results showed the barriers that teachers face in relation to the inclusion of students with ASD in their classes and also found the resistance on the part of teachers about inclusive education. Within the results, it was still evident the lack of continuing education by teachers about inclusive education, which makes it difficult to fully exercise inclusion.